AKUNTABILITAS PADA LEMBAGA AMIL ZAKAT, INFAQ DAN SHADAQAH (STUDI KASUS PADA YAYASAN DANA SOSIAL AL-FALAH (YDSF) MALANG) - Yudha Rubi Riyanti; Gugus Irianto (Jurnal Ekonomi & Keuangan Islam, 2011)
The alms organization (Lazis) is an organization which has duty to manage the donation of muslims, the biggest population of Indonesia. Therefore, implementation of accountability of such organization is necessary, considering the large amount of the potential donation that could be managed. The objective of this research is to understand the accountability practice of a well known alms organization named Yayasan Dana Sosial al Falah (YDSF) Malang branch. This is a descriptive-qualitative study. The findings of this research show that the accountability practice of YDSF Malang includes habluminallah and habluminannas dimensions. The substance of such accountability practice includes physical, mental and spiritual aspects as classify by Triyuwono and Roekhuddin (2000). Physically, the accountability practice is materialized in the responsibility report to the YDSF holding and to the benefactors. Mentally and spiritually, it is materialized into various programs both in economic and social, as well as employeesâ€™ ethic and the employeesâ€™ obedience to the Islamic law. Finally, this research proposes a variant of conventional agency theory which is stated as Islamic Agency Theory.Â